ANALISIS KEBUTUHAN PENGEMBANGAN BOOKLET BERBANTUAN AUGMENTED REALITY PADA MATERI VIRUS UNTUK SISWA SMA DENGAN BERAGAM GAYA BELAJAR - Windy Permata Sari; Rahmatika, Helsa; Yogica, Relsas; Rahmi, Fitri Olvia (CV. Jendela Gagasan, 2025)
This study aims to analyze the need for developing an augmented reality-assisted booklet on viruses for high school students with diverse learning styles. The methods used are descriptive qualitative and descriptive quantitative. Data were collected through interviews with teachers, distributing learning style identification questionnaires, and analyzing student needs. The results showed that 84.8% of students experienced difficulties in understanding the virus material. These difficulties were caused by the abstract and complex nature of the material (38.1%) and the difficulty in relating the material to everyday life (29.5%). In addition, students wanted learning materials that were interesting and efficient (60%), utilized technology in learning (43.8%), and were able to support various learning styles. The results of this study are very necessary and serve as the basis for developing an augmented reality-assisted booklet on viruses for high school students with diverse learning styles.